Effects of marketing mix strategies on intentions to purchase HIV self-test kits from pharmacies in Nairobi County - Leboo, Beatrice (Strathmore University, 2020)
Given that private institutions issue 91% of pharmaceutical products in the country, they play a critical role in ensuring that HIV self-testing kits are distributed to the populace. To achieve this, pharmacies need to be advised to implement data-driven marketing initiatives. Establishing the impact of each of the 4Ps (product, price, place, and promotion) of the marketing mix would allow creation of a more effective marketing approach; such an approach would benefit multiple stakeholders of the pharmaceutical industry in Kenya. This research sought to fill the gap by examining each of the 4Ps of the marketing mix's impact on potential customers’ purchase intentions. The study was premised on the theory of planned behaviour and the marketing mix theory. The study was grounded on a positive philosophy with a descriptive correlational design employed with quantitative data collected through questionnaires to address the objectives. The study population included the 1266 pharmacies listed in Nairobi County, with a sample of 295 pharmacies being considered in the study. The study pre-tested the study with 20 pharmacies that were not involved in the main study. Multiple linear regression was applied as the primary inferential analysis tool. The study was able to obtain an 80% response rate. The study found out that marketing mix strategies determine 15% of purchase intentions of HIV self-test kits. The study concluded that product, promotion, and price factors and age have a significant influence on customers’ purchase intentions. The research concluded that place factors, gender, and education did not significantly influence customers’ purchase intentions. The study recommends that pharmacies offer more customer-centric services such as after-sales counselling and, in partnerships with the government, create more self-test kits. The study was only limited to Nairobi County; hence there is a need for a broadened examination of acceptability of HIV self-testing kits in Kenya at large. This will help in driving the discussion on the self-test kits in the marginalized areas.
A Thesis submitted in partial fulfillment of the requirements for the award of the Degree of Masters of Business Administration at Strathmore University Business School
Keywords: Marketing mix strategies; HIV; Self-test kits; Pharmacies_Nairobi County